2017
DOI: 10.1158/1078-0432.ccr-16-0720
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Exome Sequencing of Salivary Gland Mucoepidermoid Carcinoma

Abstract: Purpose-Mucoepidermoid carcinoma (MEC) is the most common salivary gland malignancy. To explore the genetic origins of MEC, we performed systematic genomic analyses of these tumors.Experimental Design-Whole-exome sequencing and gene copy number analyses were performed for 18 primary cancers with matched normal tissue. Fluorescence in situ hybridization (FISH) was used to determine the presence or absence of the MECT1-MAML2 translocation in 17 tumors.Results-TP53 was the most commonly mutated gene in MEC (28%),… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
62
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 44 publications
4
62
0
2
Order By: Relevance
“…Although TP53 was frequently mutated in intermediate‐ and high‐grade MEC, none of the low‐grade tumours had TP53 mutations, with the only recurrent mutation in these tumours being POU6F2 (in three tumours). In addition, most tumours had a low mutational burden with many (six of nine) showing no copy number alterations . The breast MEC in our study lacked TP53 or PIK3CA mutations or complex copy number profiles typical of high‐grade triple‐negative carcinomas of no special type, and indeed showed no or only isolated genetic abnormalities aside from CRTC1 – MAML2 fusions.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Although TP53 was frequently mutated in intermediate‐ and high‐grade MEC, none of the low‐grade tumours had TP53 mutations, with the only recurrent mutation in these tumours being POU6F2 (in three tumours). In addition, most tumours had a low mutational burden with many (six of nine) showing no copy number alterations . The breast MEC in our study lacked TP53 or PIK3CA mutations or complex copy number profiles typical of high‐grade triple‐negative carcinomas of no special type, and indeed showed no or only isolated genetic abnormalities aside from CRTC1 – MAML2 fusions.…”
Section: Discussionmentioning
confidence: 57%
“…SETD2 mutations have been rarely reported in breast tumours (at most ~3% of cases), notably only in luminal A cancers and phyllodes tumours but not in triple‐negative breast carcinomas . No SETD2 alterations have been reported to date in MEC of the salivary gland, and the significance of this isolated finding in one breast MEC is uncertain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study demonstrated that M‐SGCs have heterogeneous genetic features according to histopathologic subtype. For example, molecular cytogenetic analyses have identified recurring translocations as a key genomic event in MEC ( mucoepidermoid carcinoma translocated 1 [MECT1]‐mastermind-like gene family [MAML2] ) and AdCC ( MYB‐NF1B ) . Conversely, the most recent comprehensive genomic profiling of M‐SGC indicated that ADCA and salivary duct carcinoma (SDC) have diverse genomic mutations but not specific translocations .…”
Section: Introductionmentioning
confidence: 99%
“…16,17 The fusion encodes a chimeric protein in which the Notch binding domain of MAML2 is replaced by the CREB binding, coiled-coil domain of CRTC1 fused to the transactivation domain of MAML2. 31 In this study, we retrospectively retrieved T1/2N0M0 mucoepidermoid carcinoma cases, none of which involved further treatment with PORT after complete tumor resection. 19 We and other research groups have shown that CRTC1/3-MAML2 fusions are highly specific to mucoepidermoid carcinoma, they are not detected in any other type of salivary carcinoma, [16][17][18][19][20] and that the fusions are objective markers associated with a tumor subset with lower grade histology, less advanced clinical stage, lower incidence of lymph node metastasis, and a favorable clinical course for the patient.…”
mentioning
confidence: 99%